A Test of Gravitational Theories Including Torsion with the BepiColombo Radio Science Experiment - Giulia Schettino; Daniele Serra; Giacomo Tommei; Vincenzo Di Pierri (Universe, 2020)
Within the framework of the relativity experiment of the ESA/JAXA BepiColombo mission to Mercury, which was launched at the end of 2018, we describe how a test of alternative theories of gravity, including torsion can be set up. Following March et al. (2011), the effects of a non-vanishing spacetime torsion have been parameterized by three torsion parameters, <semantics>t1</semantics>, <semantics>t2</semantics>, and <semantics>t3</semantics>. These parameters can be estimated within a global least squares fit, together with a number of parameters of interest, such as post-Newtonian parameters <semantics>γ</semantics> and <semantics>β</semantics>, and the orbits of Mercury and the Earth. The simulations have been performed by means of the ORBIT14 orbit determination software, which was developed by the Celestial Mechanics Group of the University of Pisa for the analysis of the BepiColombo radio science experiment. We claim that the torsion parameters can be determined by means of the relativity experiment of BepiColombo at the level of some parts in <semantics>10−4</semantics>, which is a significant result for constraining gravitational theories that allow spacetime torsion.